Aminothiazoles inhibit osteoclastogenesis and PGE2 production in LPS‐stimulated co‐cultures of periodontal ligament and RAW 264.7 cells, and RANKL‐mediated osteoclastogenesis and bone resorption in PBMCs. Issue 2 (1st December 2018) - Kats, Anna; Gerasimcik, Natalija; Näreoja, Tuomas; Nederberg, Jonas; Grenlöv, Simon; Lagnöhed, Ekaterina; Desai, Suchita; Andersson, Göran; Yucel‐Lindberg, Tülay
Abstract: Inflammatory mediator prostaglandin E2 (PGE2 ) contributes to bone resorption in several inflammatory conditions including periodontitis. The terminal enzyme, microsomal prostaglandin E synthase‐1 (mPGES‐1) regulating PGE2 synthesis is a promising therapeutic target to reduce inflammatory bone loss. The aim of this study was to investigate effects of mPGES‐1 inhibitors, aminothiazoles TH‐848 and TH‐644, on PGE2 production and osteoclastogenesis in co‐cultures of periodontal ligament (PDL) and osteoclast progenitor cells RAW 264.7, stimulated by lipopolysaccharide (LPS), and bone resorption in RANKL‐mediated peripheral blood mononuclear cells (PBMCs). PDL and RAW 264.7 cells were cultured separately or co‐cultured and treated with LPS alone or in combination with aminothiazoles. Multinucleated cells stained positively for tartrate‐resistant acid phosphatase (TRAP) were scored as osteoclast‐like cells. Levels of PGE2, osteoprotegerin (OPG) and interleukin‐6, as well as mRNA expression of mPGES‐1, OPG and RANKL were analysed in PDL cells. PBMCs were treated with RANKL alone or in combination with aminothiazoles. TRAP‐positive multinucleated cells were analysed and bone resorption was measured by the CTX‐I assay. Aminothiazoles reduced LPS‐stimulated osteoclast‐like cell formation both in co‐cultures and in RAW 264.7 cells. Additionally, aminothiazoles inhibited PGE2 production in LPS‐stimulated cultures, but did not affect LPS‐induced mPGES‐1, OPG or RANKL mRNA expression in PDL cells. In PBMCs, inhibitors decreased both osteoclast differentiation and bone resorption. In conclusion, aminothiazoles reduced the formation of osteoclast‐like cells and decreased the production of PGE2 in co‐cultures as well as single‐cell cultures. Furthermore, these compounds inhibited RANKL‐induced bone resorption and differentiation of PBMCs, suggesting these inhibitors for future treatment of inflammatory bone loss such as periodontitis.